BiodentineTM is cytocompatible with human primary osteoblasts - Miriam Zaccaro SCELZA; Joyce Costa NASCIMENTO; Licinio Esmeraldo da SILVA; Vinícius Shott GAMEIRO; Gustavo DE DEUS; Gutemberg ALVES (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract Calcium silicate-based materials have been widely studied due to their resemblance to, and similar applicability of, mineral trioxide aggregate (MTA). Among these, Biodentine™ (BD) was specifically designed as a "dentin replacement" material for applications such as root perforations, apexification, treatment of resorptive lesions, and as a retrograde filling material. The present study aimed to assess the in vitro response of human primary osteoblasts to BD using MTA AngelusTM as a reference material, by simultaneously analyzing three different cell viability parameters, namely mitochondrial activity, membrane integrity, and cell density. BD and MTA extracts were prepared by incubation on culture media for 24 h or 42 days after mixing. Primary human osteoblasts were exposed to extracts for 24 h, at 37oC with 5% CO2, and cell viability was evaluated by the XTT, NRU, and CVDE assays. Both materials induced cell viability levels higher than 70% when extracted for 24 h. However, when cells were exposed to extracts with increased conditioning times, MTA presented significant cytotoxic effects (p < 0.05) in comparison to the control and MTA at 24 h. After 42 days, the XTT assay identified a significant reduction in cell viability by BD when compared to the control (p<0.05), despite the fact that levels above the 70% viability cutoff were attained for biocompatible materials. It can be concluded that BD is cytocompatible with human primary osteoblasts, indicating its adequacy in direct contact with bone tissues.